Teste de microdureza Knoop em polímeros utilizados na confecção de guias cirúrgicos após o processo de desinfecção - Paulo, Beatriz Cristina de [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Objective: To analyze the Knoop microhardness of dima® Print Guide polymer samples (Kulzer – Brazil) after different disinfection methods. Material and Methods: Fifteen samples of the dima® Print Guide polymer (Kulzer – Brazil) were prepared and divided into 5 groups with 3 samples per group, namely: 1 - control group (C), in which the samples did not undergo any disinfection method; 2 - disinfected with 2% chlorhexidine (CLX); 3 - disinfected with peracetic acid (AP), 4 - disinfected with 70% alcohol (AL) and 5 - sterilized in an autoclave (EA). Three microindentations were made on the surface of each specimen with a load of 300g (c) for a residence time of 30s, which were measured using a hardness tester model HMV-G21DT (Shimadzu Corporation, Kyoto, Japan). Results: The results were submitted to the 1-factor ANOVA test, which showed statistical differences (p<0.001) and to the Tukey test. The mean values and standard deviation of the samples per group were: C (33.26±1.49a); CLX (29.71±1.69a); AP (32.23±0.33); AL (30.81±2.10a); EA (25.46±1.18b); (different letters mean statistically significant differences between the groups (p<0.05)). Conclusion: The samples sterilized in autoclave showed a decrease in microhardness and the other disinfection methods did not significantly alter the microhardness of the samples.

Objetivo: Analisar a microdureza knoop de amostras do polímero dima® Print Guide (Kulzer – Brasil) após diferentes métodos de desinfecção. Material e Métodos: Foram confeccionadas 15 amostras do polímero dima® Print Guide (Kulzer – Brasil) divididas em 5 grupos com 3 amostras cada grupo sendo eles: 1 - grupo controle (C), o qual as amostras não passaram por nenhum método de desinfecção; 2 - desinfetado com clorexidina 2% (CLX); 3 – desinfetado com ácido peracético (AP), 4 - desinfetado com álcool 70% (AL) e 5 – esterilizado em autoclave (EA). Foram realizadas três microindentações na superfície de cada espécime com uma carga de 300g(c) por um tempo de permanência de 30s, as quais foram medidas utilizando um durômetro modelo HMV-G21DT (Shimadzu Corporation, Kyoto, Japão). Resultados: Os resultados foram submetidos ao teste ANOVA fator 1, o qual mostrou diferenças estatísticas (p<0,001) e ao teste de Tukey. Os valores médios e desvio padrão das amostras por grupo foi de: C (33,26±1,49a); CLX (29,71±1,69a); AP (32,23±0,33); AL (30,81±2,10a); EA (25,46±1,18b); (letras diferentes significam diferenças estatisticamente significante entre os grupos (p<0,05)). Conclusão: As amostras esterilizadas em autoclave apresentaram diminuição da microdureza e os demais métodos de desinfecção não alteraram significativamente a microdureza das amostras.
Knoop microhardness test on polymers used in the manufacture of surgical guides after the disinfection process
Keywords: Impressão tridimensional; Cirurgia assistida por computador; Desinfecção; Esterilização; Printing, three-dimensional; Surgery, computer-assisted; Disinfection; Sterilization